Alteration of serum haptoglobin concentration in normal parturition and dystocia affected cows - D.M. Aziz; S.H. Mohammed (Iraqi Journal of Veterinary Sciences, 2016)
This study was designed to investigate the alteration in serum haptoglobin (Hp) concentration in dystocia affected cows in comparison to those having normal parturition. Thirty cows included in this study, seventeen with normal parturition and thirteen with difficult parturition (dystocia). Blood samples, from cows that having normal parturition, were collected every three days during the last two weeks of gestation, at calving, 3, 7, and 10 days postpartum. Blood samples from dystocia affected cows were collected at calving, 3, 7, and 10 days postpartum. Serum Hp concentration was determined using ELISA. The results gradual increase of Hp concentration prepartum from 190±70 mg/L at the 10th day before calving to 250±30 and 260±100 mg/L at 7th and 3rd day prepartum, respectively. At day of parturition, Hp concentration increased to 300±140 mg/L, to reach 330±150 mg/L at 3rd day postpartum. Hp concentration at 7th and 10th day postpartum declined to 230±90 and 220±160 mg/L, respectively. Serum Hp of dystocia affected cows was 360±240 mg/L at calving. At 3rd day postpartum, Hp increased to 660±220 mg/L. At 7th and 10th days postpartum, Hp concentration declined to 510±300 and 400±110 mg/L, respectively. No variation in Hp was observed between the cows giving twins and those giving single calve. There was no significant effect of dystocia causes on serum Hp at calving and at 3rd day postpartum. It be concluded that normal calving and dystocia elevated the serum Hp concentration, and insufficient dilatation of birth canal was the most effective cause of dystocia. Also comparison of serum Hp concentration at 3rd and 7th day postpartum can be used as an indicator for the development of complications.